2007
DOI: 10.1145/1290958.1290970
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the flexibility of your data warehouse

Abstract: How data warehouse flexibility affects its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…The aspects comprise positive perceptions that refer to factors that lead to their use and negative perceptions that refer to elements that discourage their usage (Silviyanti & Yusuf, 2015). The Technology Acceptance Model (TAM) was used in several previous studies on technology adoption aimed at person's acceptance of technology (Alshare et al, 2009;Baker-Eveleth et al, 2006;Davis et al, 1989;Davis & Wong, 2007;Emad et al, 2016;Goeke & Faley, 2007;Ha & Stoel, 2009;Kim & Bonk, 2006;Lin, 2008;Lin & Chou, 2009;Zaremohzzabieh et al, 2015). The Technology Acceptance Model (TAM) suggested that persons' states of mind towards another technology depend on the two key elements: Perceived Usefulness (PU) and Perceived Ease of Use (PEoU).…”
Section: The Importance Of Ict In Educationmentioning
confidence: 99%
“…The aspects comprise positive perceptions that refer to factors that lead to their use and negative perceptions that refer to elements that discourage their usage (Silviyanti & Yusuf, 2015). The Technology Acceptance Model (TAM) was used in several previous studies on technology adoption aimed at person's acceptance of technology (Alshare et al, 2009;Baker-Eveleth et al, 2006;Davis et al, 1989;Davis & Wong, 2007;Emad et al, 2016;Goeke & Faley, 2007;Ha & Stoel, 2009;Kim & Bonk, 2006;Lin, 2008;Lin & Chou, 2009;Zaremohzzabieh et al, 2015). The Technology Acceptance Model (TAM) suggested that persons' states of mind towards another technology depend on the two key elements: Perceived Usefulness (PU) and Perceived Ease of Use (PEoU).…”
Section: The Importance Of Ict In Educationmentioning
confidence: 99%
“…The technology acceptance model (TAM) has been commonly used by researchers in technology adoption studies that target users' acceptance of a technology (Alshare, Freeze, & Kwun, 2009;Baker-Eveleth et al, 2006;Davis, Bagozzi, & Warshaw, 1989;Davis & Wong, 2007;Goeke & Faley, 2007;Ha & Stoel, 2009;Kim & Bonk, 2006;Lin, 2008;Lin & Chou, 2009). TAM can provide empirical support to clarify the determinants of behavioral intention in users' adoption of ICT (Agarwal & Prasad, 1999).…”
Section: Theoretical Background and Hypothesis Testingmentioning
confidence: 99%
“…This type of system functions as a specially prepared repository of data created to support decision-making (Hartono, Santhanam, & Holsapple, 2007). Because DMT and DW have a similar characteristic, decision-support, this study reviews previous research related to the adoption of DW (Foshay, Mukherjee, & Taylor, 2007;Goeke & Faley, 2007;Gorla, 2003). Though these theoretical models are based on the TAM, they do not include social influence.…”
Section: The Task-oriented Dimensionmentioning
confidence: 99%
“…There is also an opportunity to review or investigate business intelligence (BI) tools, which are similar to DMTs, from the outlook of TAM3. Though some studies (Foshay et al, 2007;Goeke & Faley, 2007;Gorla, 2003) address the usage of data warehousing (DW) from the traditional TAM, new determinants can be considered to enhance the ability to predict and explain the usage of DW. The adoption of other BI tools, such as business analytics, automated decision systems, dashboards, or visualization tools, can also be investigated further.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation